ECRANISATION STUDY: FROM NOVEL TO FILM DILAN 1990 - Widhayani, Arrie; Suwandi, Sarwiji; Winarni, Retno (Humanus, 2018)
The purpose of this study was to describe the form of ecranitation of novels into films the Dilan 1990 by Pidi Baiq and Fajar Bustami. Ecranisation is a study in the form of transfer of vehicles or transformation from a work of art into film. The transformation in this study is different from the form of presentation. This research used qualitative using the method of content analysis. The analysis of the research was carried out in an ecranisation approach. Data were collected through library studies and sources of data from Dilan 1990 novels and films. The result of the study showed the realization of ecranisation novel and film in the 190 Dilan with new shortcomings additions and variation from the content of the story and the constituent elements of the story.Keyword: Ecranisation, Dilan 1990, Literature, film, novel Â AbstrakTujuan penelitian ini adalah untuk mendeskripsikan wujud ekranisasi dalam novel ke film Dilan 1990 karya Pidi Paiq dan Fajar Bustami. Ekranisasi merupakan kajian yang berupa alih wahana atau transformasi dari sebuah karya seni ke dalam bentuk film. Transformasi dalam kajian ini berbeda bentuk penyajiannya. Penelitian yang digunakan adalah kualitatif dengan menggunakan metode analisis isi. Analisis penelitian dilakukan pendekatan ekranisasi. Data dikumpulkan melalui studi pustaka, dan sumber data dari novel dan film Dilan 1990. Hasil penelitian menunjukkan wujud ekranisasi novel ke film Dilan 1990 adanya penciutan, penambahan, dan variasi baru baik dari isi cerita maupun unsur pembentuk ceritanya.Kata kunci: Ekranisasi, Dilan 1990, Sastra, film, novel